DAMPAK BEBAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI KANTOR PERTANAHAN KABUPATEN BERAU KALIMANTAN TIMUR - Luh Devi Candra Utami; Fakhruddin Kurnia M (Paser Institute Management and Busines, 2024)
Human resources are resources that play an important role in achieving organizational goals. Organizations such as government agencies also need good human resources to produce quality services to the community. Human resource management is basically oriented towards improving work performance. Job performance reflects the extent to which employees achieve the targets and standards set by the organization. One factor that can influence employee work performance is employee workload. This research aims to determine and analyze the influence of workload on employee work performance at Kantor Pertanahan Kabupaten Berau, East Kalimantan Province. The sample in this study was 12 respondents who were determined using random sampling in each section or section. The data analysis technique in this research uses qualitative analysis based on the results of interviews, observations and literature studies of previous research. Based on the research results, it was found that workload had a positive effect on employee work performance at the Kantor Pertanahan Kabupaten Berau.